2019
DOI: 10.1111/jan.14194
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative systematic review of the association between nurse skill mix and nursing‐sensitive patient outcomes in the acute care setting

Abstract: AimsTo examine the association between nurse skill mix (the proportion of total hours provided by Registered Nurses) and patient outcomes in acute care hospitals.DesignA quantitative systematic review included studies published in English between January 2000 – September 2018.Data sourcesCochrane Library, CINAHL Plus with Full Text, MEDLINE, Scopus, Web of Science and Joanna Briggs Institute were searched. Observational and experimental study designs were included. Mix‐methods designs were included if the quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 97 publications
2
38
0
1
Order By: Relevance
“…However, no causal inferences or pooled results were conclusive due to considerable heterogeneity in the studies' methods (Mitchell et al, 2018). Another systematic review (Twigg et al, 2019) reported an significant inverse relationship between nurse skill mix and patient outcomes. In this review, significant inverse relationship between pneumonia and infections and nurse skill mix was mentioned in fewer than 50% of the included studies: six of 13 studies and six of 15 studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no causal inferences or pooled results were conclusive due to considerable heterogeneity in the studies' methods (Mitchell et al, 2018). Another systematic review (Twigg et al, 2019) reported an significant inverse relationship between nurse skill mix and patient outcomes. In this review, significant inverse relationship between pneumonia and infections and nurse skill mix was mentioned in fewer than 50% of the included studies: six of 13 studies and six of 15 studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been found in other studies (Chang, Yen, Chang, & Liu, 2017; Kim & Bae, 2018). The indices of nurse staffing commonly used in studies are the number of nurses (e.g., the nurse‐to‐patient ratio and nursing hours per patient day) and skill mix (e.g., usually defined as the proportion of RNs or percentage of nursing hours provided by RNs) (Jacob, McKenna, & D'Amore, 2015; Twigg, Kutzer, Jacob, & Seaman, 2019). Comparatively nurses’ education, work experience and the professional–technical structures of the staff have seldom been examined (Audet, Bourgault, & Rochefort, 2018; Jacob et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐linear relationships among acuity, nurse staffing and workforce, missed nursing care (MNC) and patient outcomes are still not completely understood. The need to identify the levels of nursing staff that should be offered to warrant safe nursing care, contributing to achieve patient outcomes, is a major issue in the nursing agenda (Twigg, Kutzer, Jacob, & Seaman, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is surprising that there have been so few relevant studies at a time when nursing workforce research in general settings has been the focus of a number of important and influential studies [30] and reviews [31]. It is also noteworthy that the studies included in our review were all from the UK.…”
Section: Discussionmentioning
confidence: 99%